RANCANG BANGUN SISTEM INFORMASI KIM (KELOMPOK INFORMASI MASYARAKAT) BERBASIS WEBSITE - Ade Irmayanti; Faizal Widya Nugraha; Endah Rahmawati (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Currently, KIM of Lamandau Regency is not running well due to obstacles in the process of information management. Therefore, this research aims to design and build website-based information system that might be a solution to these problems. The existence of this information system can be aid for KOMINFO Department in coordinating KIM, communicating and disseminating information which can make society easier to search and access information.. This research uses Waterfall development method, Testing method of User Acceptance Test and System Usability Scale . The result of UAT test shows the system is successfully operated according to user needs, and the result of SUS shows that the perception of respondent to website of KIM Lamandau is at 74.05% with grade B percentile rank which means it can be used easily by new users.This is evidenced by conducting SUS testingon the KIM system to 5 categories of respondents, namely based on gender, age, male age, female age, as well as experienced and inexperienced respondens in operating a website or software that has an average range of Excellent. So, that it proves that KIM’s website for Lamandau Regency is acceptable and easy to operate by people from various circles.